Tympanoplasty type I in children - Our experience and factors affecting outcome - Melo, Ana Sofia (2017)
Objective: To analyze the success rate of tympanoplasty type I in children as well as the predictors of success.Study Design: Retrospective analysis.Methods: Review of 67 cases of children aged 6-18 years undergoing tympanoplasty type I in Centro Hospitalar e Universitário de Coimbra (CHUC) – pólo Hospital Pediátrico (HP) / Hospital Geral (HG) between January 2002 and April 2012, recorded the following variables: sex, age at surgery, etiology of the perforation, size and location of perforation, preoperative status of the contralateral ear, surgical history of operated and contralateral ear, history of prior adenoidectomy, season of surgery.Results: anatomic success rate was 77.61% and audiological success 71.64%. Statistical evaluation showed that the state of the contralateral ear is an important predictor of success.Conclusion: The study shows that timpanoplasty is a valid option in the treatment of perforated eardrum in children. The state of the contralateral ear factor seems to be a predictor of success.